The Bombs Explode at Home: Policing, Prisons, and Permanent War - Camp, Jordan T. (Social justice, 2017)
The article discusses the origins of the contemporary penal state in the U.S. Topics covered include the radical social movements of the 1960s and 1970s, Martin Luther King Jr.'s arguments against the U.S. war in Vietnam, and the link between the rise of an authoritarian neoliberal state and the global counterinsurgency against the freedom struggles that King took part in.